2020
DOI: 10.1093/ee/nvaa058
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electroantennographic Responses of Adults of Guava Weevil, Conotrachelus dimidiatus (Coleoptera: Curculionidae), to Synthetic Host-Associated and Conspecific Volatiles

Abstract: Immature guava fruits (Psidium guajava L.) of commercial orchards in Mexico are affected by adults of Conotrachelus dimidiatus (Champion) causing economic losses to producers. The aim of this study was to assess the behavioral and electrophysiological responses of the weevil to selected semiochemicals emitted by the host plant fruit and to conspecifics. Volatile organic compounds isolated from host plant as β-caryophyllene, (S)-(−)-limonene, hexanal, and nonanal significantly attracted adults of both sexes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Concerning the olfactometric response to host plant volatiles and insect volatiles, we recently reported that the most attractive volatile compound for males is β‐caryophyllene, with a similar preference of both sexes for it. In contrast, the emitted GA was preferred by females more than males, and only this C 10 terpenoid elicited a significantly different response of females and males (χ2=4.49, P =0.03) [42] …”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Concerning the olfactometric response to host plant volatiles and insect volatiles, we recently reported that the most attractive volatile compound for males is β‐caryophyllene, with a similar preference of both sexes for it. In contrast, the emitted GA was preferred by females more than males, and only this C 10 terpenoid elicited a significantly different response of females and males (χ2=4.49, P =0.03) [42] …”
Section: Resultsmentioning
confidence: 85%
“…We newly reported that the level of significance in electroantennographic responses of female C. dimidiatus to the ten volatile compounds identified in the current work was demonstrated. The guava volatile compound caryophyllene exhibited the highest antennal response (3.86±0.08 mV, F=1067.7, df=1, P =0.44 ⋅ 10 −7 ) followed by GIII+IV (3.46±0.16 mV, F=1226.4, df=1, P =0.31 ⋅ 10 −8 ), whereas P‐OL elicited the lowest response [42] . When comparing the electroantennographic responses of C. dimidiatus and C. psidii [15] toward P‐OL, the mean signal intensity was 0.78 mV±0.07 (F=4.23, df=1, P =0.03) and 1.11 mV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations